Distinct immunoglobulin heavy chain variable region gene repertoire and lower frequency of del(11q) in Taiwanese patients with chronic lymphocytic leukaemia. (23rd June 2019) - Huang, Ying‐Jung; Kuo, Ming‐Chung; Chang, Hung; Wang, Po‐Nan; Wu, Jin‐Hou; Huang, Yen‐Min; Ma, Ming‐Chun; Tang, Tzung‐Chih; Kuo, Ching‐Yuan; Shih, Lee‐Yung
Summary: Chronic lymphocytic leukaemia (CLL) is the most common leukaemia in Western countries but very rare in Asia. Peripheral blood or bone marrow mononuclear cells obtained at initial diagnosis from 194 patients with CLL were analysed to determine the ethnic difference in genetic abnormalities. Mutated IGHV was detected in 71·2% of Taiwanese CLL and IGHV3‐23 was the most frequently used gene. Stereotyped BCR was present in 18·3% with subset 8 being the most frequent. All cases with subset 8 belonged to IGHV 4‐39 and were exclusively associated with un‐mutated IGHV and poor outcome. Mutation frequencies of SF3B1 (9·7%), NOTCH1 (8·6%), BIRC3 (1·1%), ATM (16·9%) or TP53 (8·1%), and frequencies of cytogenetic abnormalities including trisomy 12 (18·6%), del(17p) (10·4%), del(13q) (43·7%) and IGH translocation (10·1%) were comparable to those reported from Western countries, except del(11q) (6·9%) which was lower in our patients. Patients with un‐mutated IGHV, subset 8, disrupted TP53, trisomy 12, and SF3B1 mutations had a worse outcome compared to patients without these mutations. In conclusion, IGHV3‐23 usage, stereotyped subset 8 and lower frequency of del(11q) show an ethnicity‐dependent association in Taiwanese CLL patients.